Perilaku Masyarakat Kampung Naga Dalam Mengelola Sanitasi dan Fasilitas Kesehatan - Fakaruddin Wahyu; Linda Kumala Sari; Muhammad Zid (Jurnal Geografi, Edukasi dan Lingkungan (JGEL), 2019)
Kampung Naga is one of indigeneous villages in Indonesia. Community of Kampung Naga are known for their strongness in preserving the traditions of their ancestral heritage. As a indigeneous village, the lives of its people are inseparable from traditional rules, including in terms of health. Eventhough, Kampung Naga is not a community who's banned Modernism. They think modernism are not prohibited, as long as it does not violate customary provisions. Sanitation issue and also health facilities is one of the issues that are often encountered in the case of indigeneous villages, including Kampung Naga. With the reality of Kampung Naga's life is still traditionally and in influence of custom, then in terms of sanitation management it also does not escape the prevailing traditional provisions. As time goes by, the more visitors come, the mindset of the people of Kampung Naga gradually changes, especially in terms of health. Today, the majority of the residents of Kampung Naga have used modern medicine through Puskesmas and also village polyclinics and are handled by medical staff such as doctors and midwives.